Pulsed Alternating Fields Magnetic Hyperthermia in Combination with Chemotherapy (5-Fluorouracil) as a Cancer Treatment for Glioblastoma Multiform: An In Vitro Study - Lilia Souiade; Miguel-Ramon Rodriguez-Garcia; José-Javier Serrano-Olmedo; Milagros Ramos-Gómez (Nanomaterials)
Inducing magnetic hyperthermia (MHT) involves locally raising the temperature to 39–45 °C, which increases the susceptibility of tumor cells to therapeutic agents without damaging healthy tissues. Recent studies on trapezoidal pulsed alternating magnetic fields (TP-AMFs) have proven their considerable efficacy in increasing the temperature of magnetic nanoparticles (MNPs) compared to sinusoidal fields. Thermal therapies have been known to incorporate multiple combinations of therapeutic approaches to optimize the medical procedure for healing cancer patients such as chemotherapy and radiotherapy. The combination of MHT with chemotherapy aims to enhance the therapeutic effects against cancer due to the synergistic interaction in tumor cells. In this study, we aim to exploit the synergistic effects of combining MHT produced by TP-AMFs with a low concentration of 5-Fluorouracil (5-FU) to optimize the therapeutic outcomes in comparison to TP-AMFs MHT alone. Hence, we exposed a glioblastoma cell line (CT2A) incubated with iron oxide nanoparticles at 1 mg/mL to two cycles of MHT employing a trapezoidal-square waveform at 200 kHz and 2 mT for 30 min for each cycle, separated by a 45 min break, both as a single treatment and in combination with 0.1 μg/mL of 5-FU. Our findings demonstrated the efficacy of the synergistic effect between MHT treatment via TP-AMFs and the 5-FU, increasing the cell death to 58.9 ± 2%, compared to 31.4 ± 3% with MHT treatment alone. Cell death was primarily driven by the necrosis pathway (47.3 ± 2%) compared to apoptosis (11.6 ± 2). The addition of 5-FU enhanced the cytotoxic effect of MHT on CT2A cells, increasing the calreticulin (CRT) positive cells to 17 ± 1% compared to 10 ± 1% as produced by MHT treatment alone. Furthermore, this combination suggests that the employed treatment approach can promote immune system activation due to the exposure of CRT in the treated cells.